Factors Influencing Assessment Practices among University Academic Staff: A Multiple Regression Analysis - Matovu, Musa; Zubairi, Ainol Madziah (Mevlana International Journal of Education (MIJE), 2014)
This study investigated the factors influencing assessment practices among academic staff in universities, in Uganda. Academic levels, type of the university, specialisation, class size, and assessment-based training were hypothesised as factors influencing the university academic staff’s assessment practices. A purely quantitative approach was adopted to collect and analyse data for this study. An Assessment Practice Inventory Modified scale was used to collect data from 321 university academic staff considering their categorisations. Using multiple regression analysis, out of the five predictors included in the model academic levels and assessment-based training were found to be significant predictors of the university academic staff’s assessment practices; (F [2, 310] = 46.331, p < .001). According to the results revealed in this study, it is recommended that universities should ensure that their academic staff rise in academic levels and also, they should provide them with assessment-based training to improve their competencies and skills in assessing students.
Keywords: Assessment practices; University academic staff; Multiple regression analysis